The Impact of Artificial Intelligence Disruption on Industrial Relations Stability in the Media Sector - Alam, Jenice Valencia; Lie, Gunardi (Riwayat: Educational Journal of History and Humanities, 2025)
The advancement of Artificial Intelligence (AI) has created a profound transformation in global labor structures, particularly within the media industry. Automation and AI-driven algorithms have begun to replace numerous human functions, from content production to digital editorial management. This phenomenon raises normative legal issues within Indonesias labor framework, as the increasing number of employment terminations (PHK) is no longer primarily caused by economic loss, but by efficiency decisions driven by technological modernization. Existing regulations, such as Law No. 13 of 2003 on Manpower and Government Regulation No. 35 of 2021, have yet to provide an adequate legal foundation to address this emerging reality. This study employs a normative juridical legal research method, focusing on the examination of positive legal norms, legal principles, and relevant labor law doctrines. The study finds that Indonesias labor law system remains reactive and unprepared to anticipate structural changes resulting from the integration of AI in the workplace. Legal protections for workers affected by automation-induced termination are not yet comprehensively accommodated within existing regulations. The research emphasizes the need for a more adaptive and progressive reformulation of labor law, positioning reskilling and upskilling policies as preventive legal mechanisms. Such legal renewal is essential to maintain a balance between industrial efficiency and the protection of workers rights amid the ongoing artificial intelligence revolution